Arctic Pollution 2002. - Arctic Monitoring and Assessment Programme (AMAP) (AMAP Secretariat, 2002)
The second AMAP State of the Arctic Environment Report, updating the 1997 AMAP assessments on Persistent Organic Pollutants, Heavy Metals, Radioactivity, and Human Health, and including a new assessment on Climate Change Effects on Contaminant Pathways. Information is presented in a clear and readable manner for the non-scientific audience; richly illustrated and prefaced by an Executive Summary with recommendations specifically addressed to Ministers of the eight Arctic countries.